2015
DOI: 10.1007/s12011-015-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cerium Oxide Nanoparticle Valence State on Reactive Oxygen Species and Toxicity

Abstract: Cerium oxide (CeO2) nanoparticles, which are used in a variety of products including solar cells, gas sensors, and catalysts, are expected to increase in industrial use. This will subsequently lead to additional occupational exposures, making toxicology screenings crucial. Previous toxicology studies have presented conflicting results as to the extent of CeO2 toxicity, which is hypothesized to be due to the ability of Ce to exist in both a +3 and +4 valence state. Thus, to study whether valence state and oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 27 publications
4
62
0
Order By: Relevance
“…Previous studies have shown that CeO 2 nanoparticles in therapeutic doses are non-toxic [14], relatively stable and accumulate in liver upon intravenous injection [15]. While some studies demonstrated toxicity of CeO 2 nanoparticles in high doses [16], it has now been shown that the toxicity is based on whether the particles exist in Ce +3 or Ce +4 and the relative ratio of Ce +3 /Ce +4 [17]. Furthermore, several studies have shown that CeO 2 nanoparticles can be used to treat stroke [18], ovarian cancer [19], cardiomyopathy [20], sepsis [21] and obesity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that CeO 2 nanoparticles in therapeutic doses are non-toxic [14], relatively stable and accumulate in liver upon intravenous injection [15]. While some studies demonstrated toxicity of CeO 2 nanoparticles in high doses [16], it has now been shown that the toxicity is based on whether the particles exist in Ce +3 or Ce +4 and the relative ratio of Ce +3 /Ce +4 [17]. Furthermore, several studies have shown that CeO 2 nanoparticles can be used to treat stroke [18], ovarian cancer [19], cardiomyopathy [20], sepsis [21] and obesity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoceria has a large number of surface defects due to oxygen vacancies at its surface, which exponentially increase per gram of material as particle size decreases 11,21,22 . Thus, ceria nanoparticles have a natural tendency to agglomerate when its surface is not functionalized.…”
Section: Introductionmentioning
confidence: 99%
“…Gd-doped CeO 2 nanopowder was prepared as previously described (Dunnick et al, 2015). Briefly, a hydrothermal method was used in which cerium (IV) ammonium nitrate and gadolinium nitrate hexahydrate were dissolved in deionized water and mixed together.…”
Section: Methodsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) was utilized to determine the changes in valence state between samples as previously described (Dunnick et al, 2015). To determine the relative size of the nanoparticles in phosphate-buffered saline (PBS), dynamic light scattering (DLS) was performed using a Nano ZS90 instrument (Malvern Instruments, Worcestershire, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation